2006
DOI: 10.1007/s11010-006-9137-3
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 signaling via the STAT3/SOCS3 pathway: Functional Analysis of the Conserved STAT3 N-domain

Abstract: The conserved N-domain of the STAT proteins has been implicated in several activities crucial to cytokine signaling including receptor recruitment and STAT activation, cooperative DNA binding and STAT-dependent gene expression. We evaluated the role of the STAT3 N-domain in the IL-6 signal transduction pathway leading to Socs3 gene expression, an essential mechanism that controls the quality and magnitude of IL-6-dependent transcriptional responses. Based on the model for STAT N-domain function in cooperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 63 publications
6
75
1
1
Order By: Relevance
“…Consequently, inhibition of the ND can affect interactions with other proteins but not phosphorylationdependent STAT3 binding to DNA. A previous report confirmed that STAT3 ND is not essential for P-STAT3 functions in normal fibroblasts (32). Conversely, native gel electrophoresis, dual-focus fluorescence correlation spectroscopy (33), and FRET data suggest that dimerization of unphosphorylated STAT3 requires the ND (34).…”
Section: St3-h2a2mentioning
confidence: 62%
“…Consequently, inhibition of the ND can affect interactions with other proteins but not phosphorylationdependent STAT3 binding to DNA. A previous report confirmed that STAT3 ND is not essential for P-STAT3 functions in normal fibroblasts (32). Conversely, native gel electrophoresis, dual-focus fluorescence correlation spectroscopy (33), and FRET data suggest that dimerization of unphosphorylated STAT3 requires the ND (34).…”
Section: St3-h2a2mentioning
confidence: 62%
“…29,39 Despite this difference, SOCS3 and IRS-1 changed minimally in C2C12 myotubes treated with rhIL-6 or SAA1 alone. Possibly, mediators other than SAA1 may be required to stimulate muscle protein degradation in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…26 We also evaluated STAT3, an IL-6 -activated transcription factor that stimulates SOCS3 expression. 29 Treatment with rhIL-6 alone led to STAT3 phosphorylation, but the addition of SAA1 and rhIL-6 led to a stronger (P Ͻ 0.05) STAT3 phosphorylation and a major increase in SOCS3 expression. Notably, the increase in p-STAT3 preceded SOCS3 expression ( Figure 7B).…”
Section: Il-6 and Saa Act Synergistically To Increase Socs3 Expressiomentioning
confidence: 88%
“…PC1-p30/Src-Dependent Activation of STAT3 Is Insensitive to SOCS3 STAT3 can participate both in a positive and negative feedback mechanism by transcriptionally upregulating its own expression 40 and that of its inhibitor SOCS3, 41 respectively. To test whether PC1-p30/Src-dependent activation of STAT3 can regulate both pathways, we used luciferase reporters driven by the native promotors of the STAT3 and SOCS3 genes, respectively.…”
Section: Regulation Of Src By the Cleaved Pc1 Tailmentioning
confidence: 99%